The Capital Market Response to The Announcement of The 2019-2024 Indonesia Onward Cabinet System : Empirical Study on Companies Listed on Kompas Index 100 - Jegarut , Clara Trimawarningsih Saravia; Rahayu, Caecilia Wahyu Estining; Yulita, Ima Kristina (Jurnal Keuangan dan Bisnis, 2021)
This research aims to examine capital market response to the 2019-2024 Indonesia Onward Cabinet System announced by President Jokowi. This event study research used market estimation model to estimate the expected return with an estimated period of 100 days and window period of seven days. There were 90 companies that are the member of Kompas Index 100 as the sample used in this research. T-test was used to analyze the data. The result shows that the announcement System of Indonesia Onward Cabinet 2019-2024 was responded positively and significantly by capital market. The result supports signaling theory in which the announcement of the 2019-2024 Indonesia Onward Cabinet System gave positive signal (influence) on capital market.